Mustafa Kemal's Instructions (An Intercepted and Decyphered Telegram) to Bekir Sami in London-a Reassessment of the London Conference (21 February - 12 March 1921) and its Immediate Consequences - Yuluğ Tekin Kurat (Türk Tarih Kurumu, 1984)
When the Greek army failed to capture Eskishehir and had to beat a retreat before the defences of İnönü in early January 1921, armed conflict gave its way to diplomacy for a while. The initiative came from the Allies, who having met in Paris on 25 January, adopted the suggestion of Count Sforza, the Italian Foreign Minister. Accordingly a conference was called in London between the Allies and the representatives of Greek and Turkish (Istanbul and Ankara) governments. The invitation underlined that the basis of talks should be the Treaty of Sevres, but subject to modifications as might have been necessitated by the passage of events.